Centipedegrass for Florida Lawns - J. Bryan Unruh; Laurie E. Trenholm; John L. Cisar (EDIS)
Centipedegrass is a slow-growing grass with low fertility requirements when compared to other Florida lawn grasses. It grows close to the ground, is medium textured, and is naturally lighter in color than other lawn grasses. Well-adapted to the climate and soils of Central and Northern Florida, it is the most common home lawn grass in the Florida Panhandle. There is now one cultivar adapted to South Florida conditions. This revised 7-page fact sheet discusses the advantages and disadvantages of this turfgrass variety, cultivars available for lawn use in Florida, establishment, maintenance, pest management, and other problems. Written by J. B. Unruh, L. E. Trenholm, and J. L. Cisar and published by the UF Department of Environmental Horticulture, April 2011.